Development and Validation of a Multimedia Package for Teaching Applied Electrical and Electronic Component of Basic Technology - Mustapha Sumaila Sani; Hassan Bello; Sunday A Okegbile (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
This study developed and validated a multimedia package for the teaching of Electrical/Electronic component of Basic Technology at the upper basic education level. It was a developmental research design. The area for this study is Kano state, North-Western Nigeria. The population consists of 291 Basic Technology teachers, out of this, 10 Basic Technology teachers, 5 instructional technologist and 5 computer specialists were purposely selected for the product evaluation based on four instruments. The findings revealed that design procedures were followed in the development of the Electricity/Electronics component of Basic Technology Instructional Package (EECOBTIP); EECOBTIP have adequately covered the curriculum content of the subject matter; EECOBTIP have met required instructional technology standards; and EECOBTIP have met the required technical standards. The study therefore recommends amongst others that Basic Technology teachers should be encouraged to prepare some aspects of their lessons in electronic form; EECOBTIP should be utilized for classroom instruction especially when teaching the Electricity/Electronics component of Basic Technology; and that similar packages should be developed for the other aspects of Basic Technology curriculum.